Formation of Self-dependence for Teenagers in Boarding School - Kolendoviča, Indra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The development of globalization, information technology and knowledge in the society has made social functioning more and more complicated. It causes a lot of new social problems (for example, social exclusion which results in reducing person’s self-dependence, when own personality is not really estimated, the identification of own needs and aims, the awareness of strong and weak points, as well as self-motivation when a teenager with a constructive approach motivates himself/herself and develops self-control thus improving self-dependence). Teenagers are not able to cope with both own life experience and they cannot perceive the aspects of social environment. A social pedagogue in work with teenagers is as an assistant and advisor, as a teacher, paying attention to such categories in teenager’s life as the improvement of self-dependence. The aim of the work is to determine pre conditions for the improvement of teenagers’ self-dependence at X Elementary school. The work includes the results of theoretical research about self-dependence, cognitions about the socialization process.